XXIe Salon de Mai. - Diehl, Gaston; Musée d'Art moderne de la Ville de Paris, Paris (Paris : Le Salon de Mai, 1965)
Singier, Gustave ; Vieira da Silva, Maria Elena ; Schneider, Gérard ; Ernst, Max ; Pignon, Edouard ; Soulages, Pierre ; Adam, Henri-Georges ; Chastel, Roger ; Brauner, Victor ; Dayez, Georges ; Cortot, Jean ; Couturier, Robert ; Jacobsen, Robert ; Man Ray ; Badia, Francisco ; Bourdonnaie, Alain de la ; Maryan, Pinchas Burstein ; Magritte, René ; Coutaud, Lucien ; Prassinos, Mario ; Charpentier, Michel ; Desnoyer, François ; Picasso, Pablo ; Cremonini, Leonardo ; Vasarely, Victor ; Camacho, Jorge ; Voss, Jan ; Rancillac, Bernard ; de Saint Phalle, Niki ; Cordesse, Louis
biografie
XXIe Salon de Mai, Musée d'Art moderne de la Ville de Paris, du 3 au 23 Mai 1965
Frans
boek